Research on the mechanical properties of hybrid Steel Fiber-Reinforced Self-Compacting Concrete based on the DIC method. - Hang Hu; Jianyi Gu; Yang Tu; Yi Zhou; Fuwei Zhu (PLoS ONE)
To investigate the influence of hybrid steel fibers on the mechanical properties of self-compacting concrete, this study systematically compared the mechanical performance of ordinary self-compacting concrete, single steel fiber-reinforced self-compacting concrete, and three types of hybrid steel fiber-reinforced self-compacting concrete through cube compression tests, four-point bending tests, and elastic modulus tests. The digital image correlation (DIC) method was employed to accurately measure the surface displacement and strain of the specimens. The results indicate that the self-compacting hybrid steel fiber concrete specimens exhibited excellent flexural-tensile performance. The incorporation of steel fibers significantly inhibited the development of macroscopic cracks, enhanced the crack resistance of the concrete, and effectively improved its brittleness. Particularly, when the fiber content was 1% 6mm + 1% 13mm + 1% 25mm, the compressive strength increased by 41.15%, the flexural strength increased by 266.41%, and the elastic modulus reached 40.82 MPa. Using the DIC method, this study successfully captured the full-field strain evolution during the failure process of the specimens. Based on the evolution of the maximum principal strain, the dynamic evolution characteristics of macroscopic and microscopic cracks on the specimen surface were thoroughly analyzed. The study found that the enhancement effect of hybrid steel fibers (HF) on concrete is primarily manifested in hindering the propagation of macroscopic cracks. This research provides important theoretical foundations and practical guidance for the engineering application of self-compacting concrete.